2013
DOI: 10.1097/cmr.0b013e32836314e3
|View full text |Cite
|
Sign up to set email alerts
|

The in-vitro spheroid culture induces a more highly differentiated but tumorigenic population from melanoma cell lines

Abstract: Cancer stem cells (CSCs) have been identified in various malignancies, and different properties have been examined to characterize CSCs: tumorigenicity in immunocompromised mice, stem cell surface markers, label-retaining properties, and proliferation as nonadherent spheres. This study explored the consistency and efficiency among these methods. Among the melanoma cell lines examined (A375, A875, MUM-2b, and MUM-2c), only A375 and MUM-2c grew as nonadherent spheres and continuously propagated in a defined seru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…Enhanced self-renewing capacity and tumorigenic potential in vivo have already been demonstrated for melanospheres [11], [12], [17]. High percentage of differentiated cells in melanospheres has also been shown [30], however, opposite results have been obtained as well [17], [18]. Fang et al [11] have shown that patient-derived melanoma spheres that contained tumorigenic cells can be both pigmented or nonpigmented.…”
Section: Discussionmentioning
confidence: 97%
“…Enhanced self-renewing capacity and tumorigenic potential in vivo have already been demonstrated for melanospheres [11], [12], [17]. High percentage of differentiated cells in melanospheres has also been shown [30], however, opposite results have been obtained as well [17], [18]. Fang et al [11] have shown that patient-derived melanoma spheres that contained tumorigenic cells can be both pigmented or nonpigmented.…”
Section: Discussionmentioning
confidence: 97%
“…Here, our focus was to use the natural affinity that galectin‐3 has for lactose‐functionalized dendrimers in order to survey galectin‐3‐mediated homotypic aggregation in three different cancer cell lines, thereby gaining insight into the mechanism by which cancer cellular aggregation occurs. A correlation between cancer cells aggregation in vitro and their metastatic potential in vivo has been demonstrated,30, 31 thus suggesting the real value of a therapeutic agent to inhibit galectin‐3‐mediated cellular aggregation. By using PAMAM dendrimers, we were able to fine‐tune the number of lactose groups on the multivalent framework, thus allowing more control over the outcome of the interaction.…”
Section: Introductionmentioning
confidence: 98%
“…We constructed two vaccine variants. For the first variant, as the source of MSCs, we generated melanospheres, using B16F10 cell culture under nonadherent conditions and medium for suspension culture [13,14]. Cells acquired from the melanospheres displayed a phenotype similar to that of MSCs, as revealed by the decreased expression of MITF and Tyrosinase, the increased expression of vascular endothelial growth factor (VEGF), and high ALDH activity, compared with parental B16F10 cells.…”
Section: Introductionmentioning
confidence: 99%